2019
DOI: 10.1590/rbz4820180123
|View full text |Cite
|
Sign up to set email alerts
|

Canola and coconut oils in the feed of European quails (Coturnix coturnix)

Abstract: The objective of this study was to evaluate the effect of the inclusion of canola and coconut oils to diets of European quail (Coturnix coturnix) over performance and carcass yield. One hundred and ninety-two quail (eight-days old) were randomly allocated to four dietary treatments with six replicates of eight birds each. The treatments were arranged in a factorial 2×2 scheme with two sources of dietary oil containing two levels of canola and coconut oils (1 and 2%). For performance variables, the final weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…However, dietary coconut has no effect on weight gain of broiler chickens 18 . In the same line dietary coconut at 1% had not negative effect in European quail performance 19 . These discrepancies in the results may be due the dietary level or the extraction process.…”
Section: Discussionmentioning
confidence: 63%
“…However, dietary coconut has no effect on weight gain of broiler chickens 18 . In the same line dietary coconut at 1% had not negative effect in European quail performance 19 . These discrepancies in the results may be due the dietary level or the extraction process.…”
Section: Discussionmentioning
confidence: 63%
“…Abreu et al (2014), evaluating meat yield in European quail at 42 days of age, found a yield of 78.39%, 27.88 and 18.95% for the carcass, breast and legs, respectively, with only leg yield one percent higher than in the present study. Veras et al (2019) studied the addition of two levels of coconut and canola oil in the diet of European quail, and found no difference between the oils in terms of cut yield, reporting that this was due to the relationship of the cuts with the genetic factors of the birds, and because similar amounts of oil were used in the different treatments. This may have happened in the present study since the same amount of oil was added to each diet.…”
Section: Resultsmentioning
confidence: 99%
“…[1,2] It was shown that the oil may promote an improved conversion of the diet and consequently productive performance of the quails. [3,4] The terms fat, oil, or lipid are generically used for a large number of compounds which show insolubility in water and solubility in organic solvents. Lipids are foods sources that are most susceptible to oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Free radicals, peroxides, and their by-products (aldehydes, ketones, hydrocarbons, and alcohols) are formed during the oxidative process, [5] which have been shown to have adverse effects on the productive performance, health status, and product quality. [4] Oils, fats, fat-soluble vitamins, and carotenoid pigments spontaneously react with oxygen during the oxidative process and suffer deterioration. [6] Lipid oxidation is the main cause of quality loss in meat and derived products, thus reducing the shelf life of products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation